Effectiveness of nurses and midwives‐led psychological interventions on reducing depression symptoms in the perinatal period: A systematic review and meta‐analysis - Tsuei‐Hung Wang; Lee‐Wen Pai; Ya‐Ling Tzeng; Tzu‐Pei Yeh; Yu‐Kuei Teng (Wiley, 2021)
Abstract Aim To evaluate the effectiveness of nurses and midwives‐led psychological interventions on the perinatal depressive symptoms. Design A systematic review and meta‐analysis based on the PRISMA guidelines. Methods Six databases were searched, including PubMed, MEDLINE, Cochrane Library, EMBASE, Web of Science and CINAHL. The search date range was before 30 September 2019. We used the Cochrane risk of bias tool to evaluate the quality of the included studies and Review Manager software 5.3 to conduct a meta‐analysis. The data were pooled using a random‐effect model. Results Studies (N = 827) were retrieved with 12 studies included. Psychological interventions provided by nurses and midwives have a significant effect on reducing perinatal depressive symptoms (RR: 0.72, 95% CI [0.64-0.82]). Among the approaches of psychological intervention, supportive counselling was the most effective (RR: 0.58, 95% CI [0.42-0.80]). The best intensity of intervention was six to eight sessions (RR: 0.66, 95% CI [0.55-0.79]).